Diagnostic utility of PRAME in distinguishing proliferative nodules from melanoma in giant congenital melanocytic nevi. (1st July 2021) - Gill, Pavandeep; Prieto, Victor G.; Austin, Mary T.; Giubellino, Alessio; Torres‐Cabala, Carlos A.
Abstract: We describe a case of a melanocytic proliferation arising in a giant congenital melanocytic nevus (CMN) and outline the potential utility of an immunohistochemical study with PReferentially expressed Antigen in MElanoma (PRAME) in distinguishing benign proliferative nodules (PN) from melanoma in this context. A 15‐day‐old girl presented with a fibrotic nodule clinically suspicious for melanoma within a giant CMN. Histopathological examination showed a predominantly intradermal melanocytic nevus with congenital features intermixing with an ill‐defined proliferation of larger melanocytes demonstrating mild‐to‐moderate cytologic atypia and increased mitotic activity. Anti‐PRAME was diffusely positive within the congenital nevus while negative within the larger proliferating cells. Chromosomal microarray analysis revealed whole chromosomal gains and losses only, consistent with a PN arising in a giant CMN. To our knowledge, PRAME expression in giant CMN, PN, and pediatric melanomas has not been previously described. Based on our experience with this case, we propose that differential patterns of PRAME expression may be present in these three lesions, allowing PRAME immunohistochemistry to potentially serve as a helpful adjunct diagnostic tool for laboratories that do not readily have access to molecular testing in rendering a diagnosis for atypical melanocytic proliferations arising in giant CMN.